TRANSPOSISI DIDAKTIK DALAM KONSEP PERTIDAKSAMAAN: SEBUAH STUDI FENOMENOLOGI - Muhammad Daut Siagian, - (2023)
This study aims to explore teacher experience through investigating how the internal transposition process (from knowledge to be taught to taught knowledge) is carried out by teachers in teaching the concept of linear inequality, as well as exploring the meaning of the concept of inequality in students through exploring their learning experiences and investigating learning obstacles. The research design with a qualitative approach using the phenomenological method was chosen to achieve the research objectives by involving 22 students in grade 11. The research results show that the nature of the order in R and the definition of "Suppose a, b ∈ R; if a-b ∈ P, then we can write it as a>b (or equivalently b<a); if a-b ∈ P ∪ {0}, then we can write it as a≥b (or equivalently b≤a), which is the basis used to derive the "rule of inequality". According to scholarly knowledge, a>b means that a-b is positive, or that the difference between a and b is greater than zero. While the meaning of a≥b is if a-b is positive and the combination is 0. However, this meaning or knowledge is not introduced or does not reach students. The research findings also show that most students understand inequality as a comparison of two values. Also, students tend to view inequality as equality. In addition, seven kinds of student concept images were obtained related to the concept of inequality, namely: multiplication and division of negative numbers do not change the sign of the inequality; generalization of the concept of linear inequalities involving absolute values in the concept of one-variable linear inequalities; there is no difference in the meaning of open and closed interval notations in expressing forms of inequality; inequalities as a tool to compare known quantities; inequalities as expressions and algebraic processes; a system of two-variable linear inequalities as a technique for solving two-variable linear inequalities. Overall, based on the exploration of students' understanding of the concept of inequality, it was found that there were learning obstacles (ontogenic, didactic, and epistemological) experienced by students.